Numerical investigation on crack growth in girth welded pipeline under various loadings - Chia, Chi Yong (2015)
Offshore pipelines often experience large plastic strains during laying or in services conditions. Defects such as fatigue cracks can commonly be found within the welded region of the pipelines. When the steel pipes are joined by girth welding, both surface and embedded cracks are inevitably initiated in welding zone. Defects are present within the materials and large plastic strains, structural failure due to fractures is highly possible. Even with an insignificant crack, its presence may cause a huge reduction in the capability of the materials during application. Thus, there is a need to investigate the crack growth on pipes. The project aims to investigate how different crack size will behave under different kind of amplitude loading. In this study, semi-elliptical shape crack is built to the surface crack in weld girth and investigated under tensile loading conditions using three dimensional elastic-plastic finite element analysis. The numerical crack growth will determine how the crack will behave. With the use of finite element software ‘ABAQUS’, detailed solid finite element analysis on half-pipe models with embedded cracks are conducted to study the crack initiation and propagation. By considering the effects of crack depth, crack breadth and different kind of amplitude loading, suitable conclusions and observations can be made.